Fruit and seed ontogeny related to the seed behaviour of two tropical species of Caesalpinia (Leguminosae) - de Padua Teixeira, S.; Carmello-Guerreiro, S. M.; Machado, SR (Blackwell Publishing, 2004)
Caesalpinia echinata and C ferrea var. ferrea have different seed behaviours and seed and fruit types. Comparison of the seed ontogeny and anatomy partly explained the differences in seed behaviour between these two species of Brazilian legumes; some differences were also related to fruit development. The seed coat in C. ferrea consisted of two layers of osteosclereids, as well as macrosclereids and fibres, to form a typical legume seed coat, whereas C. echinata had only macrosclereids and fibres. In C. echinata, the developing seed coat had paracytic stomata, a feature rarely found in legume seeds. These seed coat features may account for the low longevity of C. echinata seeds. The embryogeny was similar in both species, with no differences in the relationship between embryo growth and seed growth. The seeds of both species behaved as typical endospermic seeds, despite their different morphological classification (exendospermic orthodox seeds were described for C. echinata and endospermic orthodox seeds for C. ferrea). Embryo growth in C. ferrea accelerated when the sclerenchyma of the pericarp was developing, whereas embryonic growth in C. echinata was associated with the conclusion of spine and secretory reservoir development in the pericarp. Other features observed included an endothelial layer that secreted mucilage in both species, a nucellar summit, which grew up into the micropyle, and a placental obturator that connected the ovarian tissue to the ovule in C. ferrea. (C) 2004 the Linnean Society of London.
Keywords: Brazilwood; Caesalpinia echinata; C. ferrea; embryogeny; endosperm; stomata